From words to action: measuring corporate commitment to gender equality through sustainability reporting - Menichini, Tamara; Miccoli, Stefania Roberta; Salierno, Gennaro (European Journal of Sustainable Development, 2025)
Gender equality benefits both businesses and society. Being one of the United Nations’ Sustainable Development Goals (SDGs), SDG5 encourages organizations of all size and sectors to foster inclusive and respectful workplaces for all individuals, regardless of their gender, race, or background. Ensuring gender equality entails providing equitable access to resources, opportunities, leadership positions, and governance, and prevents all forms of gender-based discrimination. Accordingly, organizations increasingly shared voluntary disclosures with stakeholders about their strategies and actions toward achieving SDG5. Nevertheless, given its voluntary nature, sustainability reporting gives broad discretion in content definition, often leading to disclosures that are more symbolic than meaningful. The study aims to tackle this gap by proposing iGoal5, a content-based indicator designed to evaluate the completeness of organizational reporting on gender equality in the workplace. The iGoal5 evaluates the degree to which organizational sustainability reporting reflects a substantive corporate commitment to gender equality, by assessing the level of detail regarding strategic intent, implemented actions, and achieved performance. The framework offers targeted corrective actions based on the completeness of disclosures, thereby supporting organizations, particularly Small and Medium-sized Enterprises (SMEs) in strengthening their gender equality reporting and translating stated intentions into measurable and accountable practices, in alignment with broader sustainability policy goals. Keywords: Gender Equality, Gender gap, Sustainable Development Goals (SDGs), Sustainability Reporting, Content Analysis, Global Reporting Initiative (GRI), Small and Medium-sized Enterprises (SMEs)